Sanksi Hukum Korupsi dalam Islam - Abbas, Afifi Fauzi (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2020)
Islamic law, in any society and everywhere, aims to control, regulate, and serve as a means of societal control. It is an enforced system, primarily to protect individuals and the rights of society. Therefore, any act or action that could threaten the safety of any of these five fundamental principles should be considered a prohibited crime (delik). To protect and maintain these five fundamental principles and the welfare of humanity in general, Islam establishes and affirms a number of regulations, both in the form of commands and prohibitions. In certain cases, these regulations are accompanied by threats of worldly and/or hereafter punishment or sanctions if violated.